The Degree of Islamic Educational Teacher in Ajloun Governorate School They Using Blended Learning Strategy from their Perspective - Almomany, Entisar Mohammad Abdow (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree of Islamic educational teacher in Ajloun Governorate school they using blended learning strategy from their perspective, the study used the descriptive analysis approach, questionnaire has been used it consisted from (19) paragraph, the sample of study consisted from (120) female and male teacher. However, the finding of study showed that the degree of Islamic educational teacher in Ajloun Governorate school they using blended learning strategy from their perspective was moderated with average (3.48 out of 5). The finding also showed there weren’t any significant difference at (α ≤ 0.05) in the degree of using blended learning strategy from teacher perspective refers to variable of teacher's sex. Furthermore, there were significant differences at (α ≤ 0.05) according to teacher qualification for higher education.
Keywords: Blended Learning; Islamic Educational; Ajloun Governorate